2019
DOI: 10.5539/jfr.v8n4p52
|View full text |Cite
|
Sign up to set email alerts
|

Milk Adulteration: Detection of Bovine Milk in Caprine Dairy Products by Real Time PCR

Abstract: Milk adulteration is an international social problem. Consumption of adulterated milk may cause serious health problems and a great concern of the food industry has been raised. In this study, a method based on the polymerase chain reaction (PCR) principle was validated for detecting cow’s milk in goat's dairy products. A total of 40 goat's dairy products commonly consumed in Greece, were tested. Various concentrations, from 0.01 to 90%, of cows’ milk in goats’ mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(31 reference statements)
0
5
1
Order By: Relevance
“…The double peaks of the above samples demonstrated the amplification of both bovine and goat milk components (Figure 4). Using real-time PCR assays and TaqMan probes, Tsakali et al (2019) previously showed that 90% of commercial goat milk and dairy products in the Greek market were adulterated with cow's milk [7]. These results, combined with the results of our study showing a high proportion of cow's milk adulteration, are disappointing when considering the honesty of food labeling.…”
Section: Application Of the Developed Assay In Commercial Goat Milkscontrasting
confidence: 64%
See 1 more Smart Citation
“…The double peaks of the above samples demonstrated the amplification of both bovine and goat milk components (Figure 4). Using real-time PCR assays and TaqMan probes, Tsakali et al (2019) previously showed that 90% of commercial goat milk and dairy products in the Greek market were adulterated with cow's milk [7]. These results, combined with the results of our study showing a high proportion of cow's milk adulteration, are disappointing when considering the honesty of food labeling.…”
Section: Application Of the Developed Assay In Commercial Goat Milkscontrasting
confidence: 64%
“…Assessing the authenticity of dairy products is important not only from an economic perspective but also because of consumers' medical requirements (e.g., allergies to certain milk proteins), religious practices, or other personal choices [4]. Another important issue is the protection of the characteristics and reputation of traditional cheeses with Protected Designation of Origin (PDO) and Protected Geographical Indication (PGI), as described in Commission Regulation (EC) 1151/2012, which sets requirements for milk from certain species and/or in certain quantities [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The detection and analysis of adulteration in milk is often undertaken by techniques based on PCR or enzymelinked immunosorbent assay (ELISA) [14][15][16][17] . These techniques can be very fast and sensitive but are dependent on the ligand and substrate interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of DNA authentication assumes the possibility of detecting partial substitution of the declared type of milk by molecular genetic analysis of unique gene loci (Agrimonti and Marmiroli, 2018;Kalogianni, 2018;Agrimonti et al, 2019). The most common method for species identification in milk and dairy products is PCR followed by electrophoresis and hybridization-fluorescence detection of amplification products (Choopan et al, 2017;Di Domenico et al, 2017;Cosenza et al, 2019;Tsakali et al, 2019;Di Febo et al, 2020;Tsirigoti et al, 2020). Additional authentication approaches based on the length polymorphism of restriction fragments of amplified DNA (PCR-RFLP) have also found their application along with methods of hybridization, sequence, and biosensor analysis of the corresponding nucleotide sequences of mitochondrial and nuclear genes (Abdel-Rahman and Ahmed, 2007;Tillmar et al, 2013;Ripp et al, 2014;Abdelfatah et al, 2015;Beltramo et al, 2017;Kounelli and Kalogianni, Species identification of ruminant milk by genotyping of the κ-casein gene R. R. Vafin, 1 A. G. Galstyan, 2 S. V. Tyulkin, 1 Kh.…”
Section: Introductionmentioning
confidence: 99%